SOX2 and squamous cancers. (December 2020) - Porter, Linsey; McCaughan, Frank
Abstract: SOX2 is a pleiotropic nuclear transcription factor with major roles in stem cell biology and in development. Over the last 10 years SOX2 has also been implicated as a lineage-specific oncogene, notably in squamous carcinomas but also neurological tumours, particularly glioblastoma. Squamous carcinomas (SQCs) comprise a common group of malignancies for which there are no targeted therapeutic interventions. In this article we review the molecular epidemiological and laboratory evidence linking SOX2 with squamous carcinogenesis, explore in detail the multifaceted impact of SOX2 in SQC, describe areas of uncertainty and highlight areas for potential future research.